Structure matters. Real-world laboratories as a new type of large-scale research infrastructure. A framework inspired by Giddens' structuration theory. - Schneidewind, Uwe; Augenstein, Karoline; Stelzer, Franziska; Wanner, Matthias (Oekom, 2018)
In order to grasp the transformative potential of real-world laboratories, it is essential to understand them as a large-scale research infrastructure. Unlike single transdisciplinary projects and processes, real-world labs are not only about temporary interventions or knowledge integration. They are also about establishing long-lasting spaces for transformation and reflexive learning.
Keywords: Nachhaltige Entwicklung; Forschungsmethode; Wissenstransfer; Reallabor; Konzept; Fallbeispiel; Transdisziplinarität; Strukturation